Financial Management and Practices of Micro Finance Institution in Ntungamo District: A Case Study of Nyakyera SACCO. - Niwahereza, Gift (Kabale University, 2023)
Microfinance institutions comprise the processes, systems, internal controls, and practices relating to the way institutions manage revenues, expenses, assets, liabilities, and contingencies. This also involves managing risks and monitoring financial practices. The purpose of the study is to examine the financial management and practice of microfinance institutions in Ntungamo District a case of NYAKYERA SACCO. Financial management is the independent variable and the practice of Microfinance institutions is the dependent variable.